Formação de educadores: produzindo conhecimento e possibilitando mudanças sociais na comunidade - Guerra, Mônica Galante Gorini (2010)
This research is part of the Interinstitutional University Extension Program Acting as Citizens Program (PAC-LAEL-PUC-SP) in the framework of teacher continuing education based on a critical perspective, that is, the formation of critical-reflexive professionals. The main objective of this study is to understand how the chain of activities of the Extension Project Learn-Play: Children s Stories allows the creative output of the Citizenship Attitudes , that is, actions which materialize values outlined in the project, based on responsible autonomy for participants to seek solutions for problems they need facing. The references to Citizenship Attitudes topic were observed during: (a) the planning meetings of the group of researchers (b) the workshops for developing the Teacher Support Team TST (Parrilla & Daniels, 2004); (c) the teacher education meetings; (d) a class based on the discussed principles; and (e) the presentation at the Acting as Citizens Symposium. This study is theoretically grounded on a vision to develop critical-reflective professionals (Liberali, 2009c; Magalhães, 2009; Nóvoa, 1995; Pérez Gómez, 2000), on the Social-Historical-Cultural Activity Theory (Vygotsky, 1930/2003); Leontiev, 1959/1998; Engeström, 2000/2005; 2003; Daniels, 2003), on the constitution of the reflective professional focusing on the issue of language (Bakhtin, 1953/2003) and on the centrality of collaboration for teachers education (John-Steiner, 2000 and Magalhães, 2009). It adopts the critical research of collaboration methodology (Magalhães, 2009), which allows space for everyone involved to seek changes in their practices. The participants of this investigation were researchers from PAC and educators and students of daycare centers located at the east area of the city of Sao Paulo. The data were generated in 2007 through observation and audio and video recording of teacher education activities. In order to understand the production of meanings in the Creative Chain (Liberali, 2006) and to analyze the argumentation as a collaborative process, the discussion of these data were based on the analysis of theme contents (Bakhtin. 1953/2003), argumentation (Pontecorvo, 2005) and the types of arguments (Perelman & Olbrechts-Tyteca, 1996/2005) that were used. It was also analyzed the role of argumentation through the construction of the topic Acting as Citizen . The results show that argumentation provided a mutual configuration of senses (Aguiar, 2010) in the analyzed activities and, some times, it provided creative traits producing shared meanings by the groups